Optimalisasi Pemberdayaan Keluarga dan Kader Melalui Pelatihan Pendidikan Kesehatan Pengelolaan Hipertensi Lansia pada Pandemi Covid-19: Optimizing Empowerment of Families and Cadres Through Health Education Training in Hypertension Management in the Elderly the Covid-19 Pandemic - Dewi Dolifah; Delli Yuliana Rahmat; Popon Haryeti; Dedah Ningrum; Helmi Akmal Fauzan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2023)
The increase in the elderly population causes an increase in elderly cases with multiple diseases. Health problems often occur in the elderly group, one of which is the problem of hypertension. Hypertension is classified as a silent disease because the patient does not know he has this disease before doing the examination. In the current COVID-19 pandemic, the elderly are the group most at risk of experiencing seriousness that can even cause death. The involvement of various parties, such as families and health cadres, plays a vital role in empowering the community in managing the elderly with hypertension at home. Management of hypertension in the elderly can be successful if family members are involved in family empowerment programs through family assistance activities and health education to make it easier for the elderly to implement changes in health behavior. The purpose of this community service is to optimize the knowledge and skills of families and health cadres in older adults with hypertension during the COVID-19 pandemic. The method used is action research. The main target of this community service activity is 20 families with elderly hypertension and 20 health cadres. The results obtained are an increase in the knowledge and skills of families and health cadres in recognizing and anticipating symptoms of hypertension in the elderly.